2009
DOI: 10.1021/je900218z
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Properties of Amino Acids from Water to Aqueous Sodium Sulfate Solutions at 298.15 K

Abstract: Enthalpies of solution and densities of glycine, L-alanine, and L-serine in aqueous solutions of Na 2 SO 4 were measured at 298.15 K. Transfer enthalpies (∆ tr H) and transfer partial molar volumes (∆ tr V φ 0 ) of amino acids from water to aqueous solutions of Na 2 SO 4 were derived. The ∆ tr H of L-alanine are positive, and the ∆ tr H of glycine and L-serine are negative. The transfer volume of all three of the amino acids are positive. The relative order in the negative value of ∆ tr H of amino acids in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…From the literature survey, we found that in recent years there are extensive studies of volumetric properties of amino acids in aqueous solution and in mixed aqueous solutions, and the protonation constant study of amino acids in mixed aqueous solution, but very few studies have been done in aqueous saccharide solutions. …”
Section: Introductionmentioning
confidence: 99%
“…From the literature survey, we found that in recent years there are extensive studies of volumetric properties of amino acids in aqueous solution and in mixed aqueous solutions, and the protonation constant study of amino acids in mixed aqueous solution, but very few studies have been done in aqueous saccharide solutions. …”
Section: Introductionmentioning
confidence: 99%
“…In spite of this, the negative Δ tr H 0 values still indicate that electrostatic interaction between glycylglycine and salts is predominant. Comparing the Δ tr H 0 data of glycylglycine with that of glycine 23,24 in the same concentration salt solutions, the more negative Δ tr H 0 values of glycylglycine reflect the stronger interaction between glycylglycine and salts than that of glycine.…”
Section: Methodsmentioning
confidence: 99%
“…19 However, few authors have studied the behavior of protein model compounds in aqueous oxacid salts solutions. 20−22 As a part of the continuation of our studies on the thermodynamics properties of amino acids and dipeptides in aqueous oxacid salts solutions, 23,24 this work reports the transfer properties of glycylglycine from water to aqueous NaNO 3 , NaClO 4 , and Na 2 SO 4 solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 56 electrolytes are studied. Table summarizes the data and the data sources with these 56 electrolytes.…”
Section: Universal Correlationsmentioning
confidence: 99%